Organizational Consequences, Marketing Ethics and Salesforce Supervision: Further Empirical Evidence - Mengüç, Bülent (Journal of business ethics, 1998)
This study comparatively examines supervisory reactions of Turkish sales managers to potentially ethical and unethical salesperson behaviors while replicating Hunt and Vasquez-Parraga (1993). Four scenarios representing ethical and unethical conditions of over-stating plant capacity utilization and over-recommending expensive products were presented to the managers. As a result of this comparative study, it is empirically demonstrated that Turkish managers primarily rely on the inherent rightness of a behavior with a focus on the individual (i.e., deontological evaluations) in determining whether a salesperson's behaviors ethical or unethical, but the moral worth of a behavior (i.e., teleological evaluations) also play a role. Turkish managers rely both on the deontological and teleological evaluations in determining their intention to intervene through discipline and rewards. Furthermore, the results are consistent with Hunt and Vitell (1986), Etzioni's moderate deontology and inconsistent with the P-utility theory and ethical egoism.